Desenvolvimento e maturidade fisiológica de manga ‘tommy atkins’ no vale do São Francisco. - Lucena, Eliseu Marlônio Pereira de (2006)
The objective of this work was to characterize the physical, physicochemical, chemical and biochemical changes during the development of mango (Mangifera indica), cv. Tommy Atkins from anthesis to harvest, identifying the optimum harvest maturity stage in heat units. The fruits were harvested at 35, 49, 63, 70, 77, 84, 91, 98, 105 and 112 days after the anthesis (DAA), being made the following determinations: fruit external morphology; longitudinal, ventral e transverse diameters; product of the diameters; fresh and dry mass; water content and percentage; skin, Blush skin and pulp color scales; pulp luminosity, Hue angle and chroma; firmness; heat units (HU); total soluble solids (TSS); total titratable acidity (TTA); pH; TSS/TTA ratio; starch; total, reducing and nonreducing soluble sugars; total, protein and nonprotein nitrogen; crude and true protein; C vitamin; total chlorophyll and carotenoids; polymeric, oligomeric and dimeric phenolics; pectin total, soluble and high/low metoxilation degree; protopectin; solubilization pectin percentage; pectin metyhylesterase, poligalacturonase, polyphenol oxidase, peroxidase, total amylase, α- and β-amylases, α- and β-galactosidases enzymes activities; cell wall and cytosol proteins. This work has indicated that mango ‘Tommy Atkins’ reached the physiological maturity at 98 DAA, that is equivalent to 1.685,09 HU. The pulp chroma was the best fruit development stage indicator in the cultivated conditions of this study (São Francisco valley), taking into account the high coefficient of determination, R2=0,9832 (P < 0,01) and excellent correlation coefficients with pH, total soluble sugars and total carotenoids, R=0,95; 0,93; e 0,93, respectively (P < 0,01).